Your development or mine? Effects of donor-recipient cultural differences on the aid-growth nexus - Anna Minasyan (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
Development aid from the West may lead to adverse growth effects in the global South due to the neglected cultural context in the development framework. There is evidence that development agendas are mainly premised upon western thought and belief systems. Therefore, I hypothesize that the expected effect of development aid on the economic growth of recipients is impaired by cultural differences between western donors and aid recipients. I test this hypothesis empirically by augmenting an aid-growth model with proxy variables of cultural distance between donors and recipients. Namely, based on the theory of cultural transmission, I use donor-recipient weighted genetic distance, to capture vertical transmission of culture. Then, I use western education of the chief executive of the recipient country to capture horizontal transmission of culture. Results of OLS panel estimation in first differences for 1961 - 2010 period show that a one unit increase in donor-recipient genetic distance reduces the effect of aid on growth by 0.2 percentage points, if aid is increased by one percentage point. In turn, a one percentage point increase in aid yields, on average, 0.3 percentage point increase in growth after a decade, if the leader in power has western education.
Keywords: O11; O17; O19; 330; aid effectiveness; cultural differences; genetic distance; western education